Navigating healthcare pathways: Cascade of prevention and care for chronic viral hepatitis in asylum seekers and refugees. A multicenter analysis in Northern Italy - Beatrice Formenti; Roberto Benoni; Jacopo Testa; Giulia Bertoli; Giacomo Stroffolini; Maria Grazia Pizzi; Barbara Menzaghi; Niccolò Ronzoni; Paola Magro; Issa El Hamad; Carla Scolari; Angiola Spinetti; et al. (Journal of Migration and Health)
Viral hepatitis is a leading cause of mortality and a global public health challenge that, until recently, has been largely neglected as a health priority. This study describes the prevalence of viral hepatitis B and C in asylum seekers and refugees who participated in screening across three cities in Northern Italy. The analysis highlights significant pitfalls in linkage and retention in care, as well as factors associated with continuing or discontinuing the healthcare pathways, controlling for WHO Region of origin, gender, age and study site. Hospital records provided demographic and clinical data. Screening for HBV, HCV, and HIV was conducted, followed by clinical management and vaccination where appropriate. Multinomial logistic regression identified distinct care pathways. Of 1,514 participants, 80.2 % underwent screening, with 87.3 % testing negative for all infections. For those with chronic infections, 20.8 % missed their first infectious disease consultation, and only 39.3 % were retained in care after one year. Among the 591 individuals (55.8 % of the total) eligible for HBV vaccination, 10.0 % (59 out of 591) actually received the vaccine. Seven distinct care pathways were identified, where significant differences were observed based on the region of origin and the specific study site, highlighting the impact of local healthcare infrastructure and support systems. This study highlights the critical need for innovative, intersectoral and community-based approaches that are responsive to migrants' needs and perspectives. Key recommendations include enhancing linkage to care, improving followup strategies, and establishing a robust national and European network to ensure continuity of care and to integrate public health efforts across the entire care pathway and deliver fair and equitable healthcare..